2001
DOI: 10.1103/physrevb.63.224422
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxation behavior inLa0.5Ca0.5MnO3

Abstract: We have carried out a systematic magnetic relaxation study, measured after applying and switching off a 5 T magnetic field to polycrystalline samples of La 0.5 Ca 0. The above measurements suggested that the general temperature dependence of the LTLRR and the underlying physics were mainly independent of the particular charge ordering system considered. All relaxation curves could be fitted using a logarithmic law at long times. This slow relaxation was attributed to the coexistence of ferromagnetic and antife… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 25 publications
3
39
0
2
Order By: Relevance
“…While this sort of glassy behavior and the slow relaxation can be attributed to domains in ferromagnets, to superparamagnetism or to conventional spin glass phases associated with local disorder, another possibility in the phase separated materials is that the relative fractions of the different phases slowly adjust to changes in the external environment. This explanation is consistent with the observation that the relaxation effects seem to be especially pronounced in materials near x = 0.50 [8,11,15,16] where there is often a crossover between predominantly ferromagnetic conducting and antiferromagnetic charge ordered states [24] and phase separation appears to dominate the physical properties [2,25].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…While this sort of glassy behavior and the slow relaxation can be attributed to domains in ferromagnets, to superparamagnetism or to conventional spin glass phases associated with local disorder, another possibility in the phase separated materials is that the relative fractions of the different phases slowly adjust to changes in the external environment. This explanation is consistent with the observation that the relaxation effects seem to be especially pronounced in materials near x = 0.50 [8,11,15,16] where there is often a crossover between predominantly ferromagnetic conducting and antiferromagnetic charge ordered states [24] and phase separation appears to dominate the physical properties [2,25].…”
Section: Introductionsupporting
confidence: 89%
“…Indeed logarithmic time dependence has been observed in the relaxation of both resistivity and magnetization after sudden changes in magnetic field [7,8,9,10,11,12,13,14,15,16,17], and there have been numerous reports of spinglass-like behavior in these materials [18,19,20,21,22] (although the qualitative details of the behavior are not necessarily consistent with the conventional behavior of spin glasses [23]). While this sort of glassy behavior and the slow relaxation can be attributed to domains in ferromagnets, to superparamagnetism or to conventional spin glass phases associated with local disorder, another possibility in the phase separated materials is that the relative fractions of the different phases slowly adjust to changes in the external environment.…”
Section: Introductionmentioning
confidence: 99%
“…Lopez et al [11] have provided evidence for two competing magnetic phases in La 0. employing measurements of low-field dc magnetization, ac susceptibility, magnetic relaxation and memory effects. The study has revealed the presence of glassy magnetic phases in both these manganates, albeit of different varieties.…”
Section: Introductionmentioning
confidence: 99%
“…This point has been confirmed through both structural studies and the measurement of magnetic properties 1,2 but the analysis of its consequences on the extrinsic magnetic properties ͑hysteretic and relaxational behavior͒ still requires a substantial amount of research. 3 Our purpose here is to measure the temperature dependence of the low-field magnetization as well as those of the hysteretic and relaxational parameters in two La manganite samples including different amounts of oxygen. The results will be discussed in terms of the magnetic phase distribution of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…The results will be discussed in terms of the magnetic phase distribution of the samples. 3.12 ͒ was prepared using the same heating conditions and cooling the powders in oxygen inside the furnace at 2°C / min down to room temperature. The cationic composition was determined by inductive coupling plasma and electron probe microanalysis.…”
Section: Introductionmentioning
confidence: 99%